Writing strategies for all primary students scaffolding independent writing with differentiated mini-lessons, grades K-3 - Richards, Janet C. 1936-; Lassonde, Cynthia A. (Jossey-Bass teacher., 2011)
"A guide for teaching all your students the skills they need to be successful writers The 25 mini-lessons provided in this book are designed to develop students' self-regulated writing behaviors and enhance their self-perceived writing abilities. These foundational writing strategies are applicable and adaptable to all primary students: emergent, advanced, English Language Learners, and struggling writers. Following the SCAMPER (Screen and assess, Confer, Assemble materials, Model, Practice, Execute, Reflect) mini-lesson model devised by the authors, the activities show teachers how to scaffold the writing strategies that students need in order to take control of their independent writing. · Reveals helpful writing strategies, including making associations, planning, visualizing, accessing cues, using mnemonics, and more · Offers ideas for helping students revise, check, and monitor their writing assignments · Explains the author's proven SCAMPER model that is appropriate for students in grades K-3 Let Richards and Lassonde--two experts in the field of childhood education--guide you through these proven strategies for enhancing young children's writing skills"--Provided by publisher.